Effect of Gamma Irradiation on Dielectric Permitivity of Polymer (PVA-CH) Film - Susilawati Susilawati; Aris Doyan (Department of Physics Education, Universitas Mataram, 2018)
The objectives of this study are to investigate the effects of radiation on dielectric properties of PVA-CH films. Polymer (PVA-CH) films were irradiated with Gamma ray at 12 kGy. Polymer film containing PVA (poly Vinyl Alcohol) and Chloral Hydrate (CH) has been prepared by solution casting technique. The obtained polymer composite layers were irradiated with ÃÂ³ Ã¢â¬â rays at various doses to investigate the radiation effect on dielectric permittivity in the frequency range of 20 Hz Ã¢â¬â 1 MHz at room temperatures. The real (ÃÂµÃ¢â¬â¢) and imaginary (ÃÂµÃ¢â¬Â) dielectric constant are found to increase with increase in irradiation dose.